QUALIFICATIONS FRAMEWORK DEVELOPMENT AND QUALIFICATIONS RATING IN THE LAND MANAGEMENT SPHERE - A. A. Myrasheva; E. M. Chepurin; N. R. Kamynina (Образование и наука, 2015)
The aim of the research is to observe the existing approaches to qualifications framework development in the sphere of land management, cadastres and real estate management, as well as the qualifications framework adaptation to European system. The relevance of the issue is related to the specific professional and institutional problems facing Russian educational establishments engaged in personnel training in the given sphere. The authors demonstrate the qualifications framework development in the land management sector regarding it as a key mechanism of educational mobility and the router for knowledge acquisition and updates. The qualifications framework is referred to as a systematic and structured description of recognized qualifications. The accepted worldwide methodology of organizing the educational process and quality control system is given. The emphasis is on the need to comply the qualifications framework with the Russian State Educational Standards.